Discrepancies On Burn Management Knowledge Among General Physicians In West Nusa Tenggara, Indonesia - Badariyatud Dini; Nyoman Putu Riasa (Journal of Islamic Medicine, 2022)
Background:: ISBI Practice guidelines (PGs) for burn care are designed to improve burn care in resource-limited setting (RLS) and also become the standard of burn care. Discrepancy of burn care knowledge among emergency physicians will influence the implementation of ISBI PGs. Objective: of this study is to determine the discrepancy of burn care knowledge among the general physicians working in emergency unit of public hospitals in West Nusa Tenggara, Indonesia. Method: Validated questionnaires were distributed to emergency unit of 12 hospitals in West Nusa Tenggara, Indonesia. The questionnaire consist of 9 topics regarding: (a) burn center description, (b) referral criteria, (c) complications of burn trauma, (d) initial assessment, (e) burn extent calculation, (f) initial resuscitation, (g) monitoring, (h) inhalation injury and (i) wound management. Each topic consists of 10 questions or statements regarding burn care with ISBI PGs as the reference. The score for each question was 1 or 0. Total score of each topic was 10. The total score was divided into 3 categories (low score was 0-30, moderate score was 31-60 and high score was 61-90). Result: As many as 94 questionnaires were returned out of 108 questionnaires that were distributed. As many as 78% of respondents had high knowledge score while the remaining 22% of respondents had moderate knowledge score. Conclusion: The majority of emergency physicians in West Nusa Tenggara had high knowledge level of burn care. The lowest knowledge level is on initial burn assessment and resuscitation, monitoring of burn resuscitation and burn wound management topics